Orally Administrable Therapeutic Nanoparticles for the Treatment of Colorectal Cancer - Ying, Kangkang; Bai, Bingjun; Gao, Xing; Xu, Yuzi; Wang, Hangxiang; Xie, Binbin (Frontiers in Bioengineering and Biotechnology, 2021)
Colorectal cancer (CRC) is one of the most common and lethal human malignancies worldwide; however, the therapeutic outcomes in the clinic still are unsatisfactory due to the lack of effective and safe therapeutic regimens. Orally administrable and CRC-targetable drug delivery is an attractive approach for CRC therapy as it improves the efficacy by local drug delivery and reduces systemic toxicity. Currently, chemotherapy remains the mainstay modality for CRC therapy; however, most of chemo drugs have low water solubility and unstable in the gastrointestinal tract (GIT), poor intestinal permeability, and are susceptible to P-glycoprotein (P-gp) efflux, resulting in limited therapeutic outcomes. Orally administrable nanoformulations hold the great potential for improving the bioavailability of poorly permeable and poorly soluble therapeutics, but there are still limitations associated with these regimes. This review focuses on the barriers for oral drug delivery and various oral therapeutic nanoparticles for the management of CRC.